Finiteness and nominalization - Chamoreau, Claudine; Estrada Fernández, Zarina (Typological studies in language, 2016)
This volume addresses the relation between finiteness and nominalization, which is far more complex than the simple opposition finite-nonfinite. The contributions analyze finiteness cross-linguistically from both synchronic and diachronic perspectives, focusing on a number of topics that has not been thoroughly explored in the literature.